Loss of early B cell protein λ5 decreases bone mass and accelerates skeletal aging - Khass, Mohamed; Rashid, Harunur; Burrows, Peter D.; Javed, Amjad; Schroeder, Harry W. (Frontiers in Immunology, 2022)
The early B cell protein λ5 is an essential component of the surrogate light chain and the preB cell receptor (preBCR), which is critical for optimal B cell development. To investigate the effect of λ5 and/or B cells on bone acquisition over time, we developed a panel of λ5-/-, JH-/-, λ5-/-JH-/-, and wild type (WT) BALB/c mice. We studied postnatal bone development and aging at one, six, twelve, and twenty-two months of age in these mice. The trabecular bone volume over total volume (BV/TV) in JH-/- mice was similar to WT at all ages. In contrast, at six-months of age and thereafter, λ5-/- and λ5-/-JH-/- mice demonstrated a severe decrease in trabecular bone mass. Surprisingly, bone mass in six-month-old λ5-/- and λ5-/-JH-/- mice was similar to or even lower than aged (twenty-two-months) WT mice, suggesting accelerated skeletal aging. The postnatal development and the acquisition of cortical bone mass in λ5-/- and JH-/- mice were generally comparable to WT. However, λ5-/-JH-/- mice showed a significant decrease in cortical BV/TV at six- and twelve-months of age. To examine the contribution of λ5 and B cells in postnatal bone synthesis, we separately transplanted whole bone marrow cells from λ5-/-JH-/- and WT mice into irradiated λ5-/-JH-/- and WT recipients. Transplant of λ5-/-JH-/- marrow cells into WT recipients failed to show acquisition of trabecular bone mass, whereas transplanting WT marrow cells into λ5-/-JH-/- recipients led to the recovery of trabecular bone mass. Transfer of WT marrow cells into λ5-/-JH-/- mice promoted synthesis of new cortical and trabecular bone. Our findings indicate that λ5 plays a major role in preserving bone mass during postnatal development and skeletal aging that is distinct from its role in B cell development. The absence of both λ5 and B cell in λ5-/-JH-/- mice leads to delayed acquisition of cortical bone during postnatal development. Dissecting the mechanism(s) by which λ5 regulates bone homeostasis may provide new avenues for the treatment of age-related loss of bone mass and osteoporosis.